ACT: a framework for effective theories of change and activities in agri-food system transformation initiatives - Freed, Sarah Johanna; Rietveld, Anne (2025)
The ACT Framework for Agency and Behavior Change in Transforming Agri-food Systems has been used by researchers to 1) guide them in applying a systems approach in understanding the diversity of food system actors and their opportunities for change; and 2) systematically identify, prioritize, and leverage the factors influencing actors’ agency and behaviors. In Burkina Faso, this approach contributed to developing an inclusive, agroecological business model for the dairy value chain. Alliance researchers played a key role in developing and implementing the framework.